2015
DOI: 10.1016/j.jaci.2014.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Role of siglecs and related glycan-binding proteins in immune responses and immunoregulation

Abstract: Eukaryotic cells and extracellular material are heavily decorated by various glycans, yet the understanding of the structure and function of these moieties lags behind our understanding of nucleic acids, lipids and proteins. Recent years have seen a tremendous acceleration of understanding in the field of glycobiology, revealing many intricacies and functional contributions that were previously poorly understood or even unrecognized. This review highlights several topics relevant to glycoimmunology, where mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 116 publications
0
74
0
Order By: Relevance
“…Not only proteins but also carbohydrates can stimulate the production of IgE antibodies and be strong inducers of 2 responses [33]. e current estimate is that 15-30 % of allergic patients generate speci c anti-carbohydrate IgE antibodies [34], but this IgE response has very little clinical relevance [35].…”
Section: Features Of the Immune Response To Carbohydratesmentioning
confidence: 99%
“…Not only proteins but also carbohydrates can stimulate the production of IgE antibodies and be strong inducers of 2 responses [33]. e current estimate is that 15-30 % of allergic patients generate speci c anti-carbohydrate IgE antibodies [34], but this IgE response has very little clinical relevance [35].…”
Section: Features Of the Immune Response To Carbohydratesmentioning
confidence: 99%
“…This approach is still the most reliable method for obtaining detailed structural information about the protein-modifying carbohydrates as the protein-level heterogeneity, both in terms of site occupancy and the number of site-specific structures, represent exceptional challenges for analysis. However, information about protein and site-specific glycosylation is lost by this approach, so there is a growing need for routine glycopeptide analysis, as glycosylation has been implicated as a key player in cell-cell interactions, host/pathogen interactions, enzymatic processing, and even intracellular signaling (7)(8)(9)(10)(11)(12)(13). Studies have shown that glycosylation is species-, and tissuespecific, and can be altered by disease or physiological changes (14 -22).…”
mentioning
confidence: 99%
“…Additional examples that are especially relevant to allergic diseases are detailed in an accompanying paper in this volume. 9 …”
Section: Glycans and Glycan Binding Proteins In Immune Regulationmentioning
confidence: 99%
“…Examples relevant to lung inflammatory diseases are discussed in more detail in an accompanying review in this issue. 9 Siglecs function by binding to sialoglycans on their own cell surfaces, on other cells and tissues, and/or on sialic acid-bearing pathogens. 21 The interplay of sialic acids and sialic acid recognition in immune regulation, pathogenesis, and pathogen recognition results in something of an evolutionary arms race as pathogens and hosts respond to changing glycan landscapes.…”
Section: Glycans and Glycan Binding Proteins In Immune Regulationmentioning
confidence: 99%
See 1 more Smart Citation